Reorganization Of PT Pertamina (Persero) And Its Impact On Status Holding Company From The Viewpoint Of Beneficial Ownership Of The Business - Ivanovenska Ardya Aqilla Yudhistira (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
Corporate restructuring is a common thing to do in favor of performance efficiency. But what if it is StateOwned Enterprises undergoes a restructuring? Internal restructuring of State-Owned Enterprises is actually not a new thing, an inefficient organizational structure certainly requires an update, but what if the restructuring of a State-Owned Enterprises resulted in the formation of a Holding Company? What are the juridical implications about the status of the Holding Company? The juridical basis for the formation of a State-Owned Enterprises Holding Company used so far is Government Regulation No. 72 of 2016 concerning procedures for state capital participation in State-Owned Enterprises and Limited Liability Company. Because of this background, the researcher will examine the regulation of State-Owned Enterprises Holding Company in Indonesia and its impact on the status of subsidiaries incorporated in PT Pertamina as a State Owned Enterprise in the oil and gas sector.